The Effects of Learning Activities on Waste and Sewage Management Using Question and Problems-Based Learning for Undergraduate Students of Mahasarakham University, Thailand - Uraiwan Praimee; Wannasakphijit Boonserm (Journal of Educational Issues, 2024)
In this study, the purposes of this research were to study and compare knowledge about waste and sewage management, environmental ethics and environmental volunteers using question and problems-based learning, before and after class of undergraduate students, to compare knowledge about waste and sewage management, environmental ethics and the environmental volunteers of undergraduate students with different gender and Grade Point Average (GPA). The sample used in the research were 111 undergraduate students being selected by purposive sampling who were enrolled in the course control waste and sewage in the 1st semester of the academic year 2019. The research tools were a learning activity plans on solid waste and sewage management using question and problems-based learning, knowledge test on waste and sewage management, environmental ethics test and environmental volunteers test. The statistics used in the research were frequency, percentage, mean, standard deviation, including hypothesis testing using t-test, F-test (One-Way MANOVA, One-Way MANCOVA) and Univariate Test. The results showed that: (1) The undergraduate students had an average score of knowledge about waste and sewage management, environmental ethics and environmental volunteers in the posttest was higher than the pretest statistical significance (p < .05); (2) There was no different of knowledge score of waste and sewage management, environmental ethics and environmental volunteers of undergraduate students with different gender (p > .05); (3) There was statistical significant different of knowledge score of waste and sewage management, environmental ethics and environmental volunteers of undergraduate students with different Grade Point Average (GPA) (p < .05).